IMPROVING STUDENTS' WRITING SKILL USING COLLABORATIVE WRITING AT THE SECOND GRADE OF SMA N 1 ANDONG BOYOLALI IN 2010/2011 ACADEMIC YEAR - Abdillah, Satriyo Yoga Aji (2011)
This research aims at describing the implementation of teaching writing using collaborative writing in improving students' writing skill at the second grade of SMA N 1 Andong Boyolali in 2010/2011 academic year, describing the improvement of students' writing skill and describing the students' responses on the implementation of students' writing skill using collaborative writing at the second grade of SMA N 1 Andong Boyolali in 2010/2011 academic year. The sources of data are taken from event, informant, and document. The methods of collecting data are observation, test, interview, and documentation. To analyze the data the researcher compared the results of pre-test and post-tests as descriptive comparative and critic analysis technique. The results of the research show that: 1) collaborative writing is effective in improving students' writing skill. 2) The students' scores of post-tests are significant higher than pre-test scores. It can be seen from the average score that improve 42.98. The mean score of pre test is 36.32 and the mean score of post-test is 79.30. 3) The students are interested in learning writing using collaborative writing. Finally, the researcher concludes that collaborative writing technique can improve the students' writing skill for the second grade of SMA N 1 Andong Boyolali.